Optical Sensor for Indian Siddha Diagnosis System - Deepa, N.; Ganesh, A. Balaji (Procedia engineering, 2012)
Traditional Indian medicine has been using the pulse as a form of disease diagnosis. The roots of this pulse diagnosis lie in the three radial pulses which are known as vata, pitta, and kapha. In this project, a photoplethysmographic sensor is presented for pulse diagnosis. PPG sensor is used to monitor the blood flow rate. The sensor is placed at identified radial points corresponding vatta, pitta, kapha. The output of the sensor is analyzed using Lab VIEW software.PPG values are taken at wrist for subjects in different age groups. The acquired PPG signal is compared with the values taken by the Siddha Practitioner and classified the subjects as of vata, pitta, and kapha type.